Characterization of an Antiviral Component in Human Seminal Plasma - Chen, Ran; Zhang, Wenjing; Gong, Maolei; Wang, Fei; Wu, Han; Liu, Weihua; Gao, Yunxiao; Liu, Baoxing; Chen, Song; Lu, Wei; Yu, Xiaoqin; Liu, Aijie; et al. (Frontiers in Immunology, 2021)
Numerous types of viruses have been found in human semen, which raises concerns about the sexual transmission of these viruses. The overall effect of semen on viral infection and transmission have yet to be fully investigated. In the present study, we aimed at the effect of seminal plasma (SP) on viral infection by focusing on the mumps viral (MuV) infection of HeLa cells. MuV efficiently infected HeLa cells in vitro. MuV infection was strongly inhibited by the pre-treatment of viruses with SP. SP inhibited MuV infection through the impairment of the virus’s attachment to cells. The antiviral activity of SP was resistant to the treatment of SP with boiling water, Proteinase K, RNase A, and DNase I, suggesting that the antiviral factor would not be proteins and nucleic acids. PNGase or PLA2 treatments did not abrogate the antiviral effect of SP against MuV. Further, we showed that the prostatic fluid (PF) showed similar inhibition as SP, whereas the epididymal fluid and seminal vesicle extract did not inhibit MuV infection. Both SP and PF also inhibited MuV infection of other cell types, including another human cervical carcinoma cell line C33a, mouse primary epididymal epithelial cells, and Sertoli cell line 15P1. Moreover, this inhibitory effect was not specific to MuV, as the herpes simplex virus 1, dengue virus 2, and adenovirus 5 infections were also inhibited by SP and PF. Our findings suggest that SP contains a prostate-derived pan-antiviral factor that may limit the sexual transmission of various viruses.